குழந்தைகள் கலைக்களஞ்சியம் : தொகுதி - 3 - (:unkn) unknown (International Institute of Tamil Studies, Chennai, 1983)
This book imparts general encyclopedic knowledge about various subjects, especially for children.
Tamil Encyclopedia Kalaikkalanjiyam (Children) : Volume-3
Keywords: Tamil; Encyclopedia; Tamil